PERSEPSI GURU PJOK DALAM HAL PROSES PEMBELAJARAN DAN KESULITAN PEMBELAJARAN PJOK SECARA DARING DI SMA NEGERI AKIBAT PANDEMI COVID-19 SE KABUPATEN BANDUNG - Mohammad Fakhri Dwi Ajiputra, - (2022)
The occurrence of the COVID-19 pandemic had an impact that learning had to be changed in the way it was delivered, namely conventional learning into distance learning (DL), which is also known as online learning. Online learning has consequences for PJOK teachers, namely teacher perceptions, online learning process strategies, difficulties experienced and how to overcome these difficulties. This study aims to describe the perception of PJOK teachers with all the consequences for online learning in SMA Negeri in Bandung Regency. This study uses a qualitative descriptive approach with research subjects PJOK teachers in SMA N in Bandung Regency. Sampling using the Two Stage Cluster sampling technique and obtained 8 PJOK teachers from 8 SMA N in Bandung Regency. Research data collection techniques were carried out through observation, semi-structured interviews, and documentation. The data collection instrument used observation guidelines and interview guidelines. Analysis of research data using the NVivo 12 application. The results showed that 1) PJOK teachers' perceptions consisted of positive perceptions and negative perceptions; 2) PJOK teachers' online learning process strategies include strategies for implementing online learning processes, strategies for assigning assignments to students, and evaluation strategies in the online learning process; 3) Difficulties experienced by PJOK teachers in the online learning process include 3 factors, namely teacher and student factors, technical factors, and social factors; 4) Efforts to overcome difficulties in the online learning process, namely for teacher factors including increasing skills in the ICT field, especially in online learning, increasing online learning planning abilities, increasing abilities in making interesting and creative learning materials; for technical factors, it is necessary to fulfill the need for facilities and infrastructure related to online learning, namely internet access, mobile phones, laptops or computers; while social factors increase the ease of interaction between students and teachers including access to interactive online learning media such as virtual classes and good social media access.